The investigation of novel Benzimidazoles as anti-cancer agents in triple negative breast cancer cell lines - Smit, Christie Jane (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Bioinformatics)
Access restricted. Exxpected release in 2026.
Keywords: Uncatalogued